2021
DOI: 10.33590/emjreprohealth/21-00015
|View full text |Cite
|
Sign up to set email alerts
|

Examining Diagnostic Options and Classification Systems Available for Endometriosis

Abstract: Introduction: Endometriosis is characterised by the presence of endometrium-like tissue outside the uterus, and is often associated with chronic pelvic pain, infertility, and compromised quality of life. Development of reliable methods of early diagnosis, staging, and classification of endometriosis would allow for restriction of disease progression by its early detection and strategising towards its early treatment and management. Diagnostic options: Typically, diagnosis and staging of endometriosis include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Growth of endometrial tissue outside the uterus, frequently but not exclusively, in the pelvic structures gives rise to endometriotic lesions in the peritoneum (peritoneal endometriosis), the ovary (ovarian endometriosis or endometrioma), and the deep pelvis (deep infiltrating endometriosis), and infrequently in the distant organs. 1 According to Sampson's theory, deposits of viable endometrial cells following their reflux into the peritoneal space via the fallopian tubes during menstruation may adhere and grow, and give rise to endometriosis. 2 In an elegant review, Redwine 3 challenged this theory and demonstrated, by analysing a large number of parameters, that endometriosis tissue is primarily reflected dissimilarity than similarity with eutopic endometrium in the uterus, including inadequate secretory differentiation in endometriotic cells under progesterone dominance during the luteal phase.…”
Section: Introductionmentioning
confidence: 99%
“…Growth of endometrial tissue outside the uterus, frequently but not exclusively, in the pelvic structures gives rise to endometriotic lesions in the peritoneum (peritoneal endometriosis), the ovary (ovarian endometriosis or endometrioma), and the deep pelvis (deep infiltrating endometriosis), and infrequently in the distant organs. 1 According to Sampson's theory, deposits of viable endometrial cells following their reflux into the peritoneal space via the fallopian tubes during menstruation may adhere and grow, and give rise to endometriosis. 2 In an elegant review, Redwine 3 challenged this theory and demonstrated, by analysing a large number of parameters, that endometriosis tissue is primarily reflected dissimilarity than similarity with eutopic endometrium in the uterus, including inadequate secretory differentiation in endometriotic cells under progesterone dominance during the luteal phase.…”
Section: Introductionmentioning
confidence: 99%